Pengaruh Konsentrasi Surfaktan Non-Ionik Terhadap Viskositas Perekat Polivinil Asetat Berbasis Air: Effect of Non-Ionic Surfactant on Water-Based Adhesive Viscosity - Rony Pasonang Sihombing; Robby Sudarman; Agustinus Ngatin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2020)
Substrate combining could be done by using adhesive. In Indonesia, especially industrial field, solvent base adhesives were still being developed. This kind of adhesive was not environmental friendly and not safe handling. Therefore, Polyvinyl Acetate (PVAc) water-based adhesive was prepared as an outcome of this research as one of solution to overcome the problem above. Effect of surfactant concentration on the viscosity was aimed at this research. Semi continuous polymerization with stirring motor rates on 50 – 500 rpm was used (optional). Pressure of 1 atm, 750C temperature, 5 – 6 hours reaction time for each was used as polymerization operation in this research. Vinyl Acetate Monomer (VAM), partial hydrolysis Polyvinyl Alcohol (PVOH), water, Ammonium Persulfate (APS) were prepared as raw material. NP-10 and NP-06 were non-ionic surfactants which each concentration was varied in this research. Water-based adhesive with NP-06 concentration variation resulting in viscosity from 98 m.Pa for 0.17 %wt concentration to 213 m.Pa for 0.68 %wt concentration. While NP-10 concentration variation resulting viscosity from 143 m.Pa for 0.17 %wt to 321 m.Pa for 0.68 %wt concentration. Therefore, adhesive with NP-10 surfactant concentration variable has a higher viscosity rate than NP-06 ones. Keywords: Water-based adhesive, non-ionic surfactant, adhesive viscosity